Insight into Long Term Sea Level Change Based on New Tide Gauge Installations at Takoradi, Aden and Karachi - Woodworth, Phillip; Foden, Peter; Pugh, Jeff; Mathews, Andrew; Aarup, Thorkild; Aman, Angora; Nkebi, Emmanuel; Odametey, Joseph; Facey, Roy; Esmail, Mustafa Yousef Abdulgafor; et al. (The International Hydrographic Review, 2009)
Three sea level stations with extensive historical information have recently been equipped with new technology tide gauges, following large gaps in recording at the stations. The new and historical data in combination provide information on the rates of sea level rise along parts of the global coastline not wellrepresented in scientific studies to date. In these cases, the rates were found to be similar to those observed at many other locations around the world. However, it is suggested that other stations, where historical data exist and where gaps in recording have occurred, could be similarly equipped with new gauges, thereby expanding the spatial coverage of our knowledge of sea level rise.